2004
DOI: 10.1021/jo0485280
|View full text |Cite
|
Sign up to set email alerts
|

General Method for the Preparation of β,β-Difluoroacrylates Using BrF3

Abstract: Various esters were reacted with base, carbon disulfide, and methyl iodide, producing 2-carboalkoxy-1,1-bis(methyl sulfide)-1-alkenes (2). The reaction of 2 with BrF(3), followed by oxidation with HOF.CH(3)CN gave the bromodifluorosulfonyl derivatives 5. Subsequent treatment with Raney nickel led to alpha-substituted beta,beta-difluoroacrylates 6 in overall yields of 50-80%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…Recently, we have shown that b,b-difluoroacrylates can be synthesized using bromine trifluoride [12]. We are describing here yet another method, using similar starting materials leading to an efficient synthesis of various difluorovinyl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have shown that b,b-difluoroacrylates can be synthesized using bromine trifluoride [12]. We are describing here yet another method, using similar starting materials leading to an efficient synthesis of various difluorovinyl compounds.…”
Section: Resultsmentioning
confidence: 99%
“…[48] A somewhat similar approach to the one described in Scheme 14, was also adopted for the synthesis of N-trifluoromethyl amides. Several different imides or amides were reacted with tris(methylthio)methyl tetrafluoroborate (72). [49] The resulting N À CA C H T U N G T R E N N U N G (SMe) 3 derivatives of phthalimide (73), and caprolactam (74) were treated with bromine trifluoride to produce the N-trifluoromethylphthalimide (75) [50] and N-trifluoromethylcaprolactam (76) both in 60% yield (Scheme 20).…”
Section: Forming the Cf 3 Groupmentioning
confidence: 99%
“…with Raney nickel they produced a whole series of the important difluoroacrylic acids 119 in reasonable yields (50 to 80%) (Scheme 29). [72] A related reaction, resembling the Wittig methylation of carbonyls, was developed for converting aldehydes and ketones to 1,1-difluoroolefins with the aid of BrF 3 . The lithium salt of the commercial bis(methylthio)methane (120) was reacted with TMSCl to produce bis(methylthio)trimethylsilylmethane (121) which when reacted with either ketones or aldehydes formed 1,1-bis(methylthio)alkene derivatives 122.…”
Section: Forming the Cf 2 Groupmentioning
confidence: 99%
“…
explored as new materials because of their superconducting, optical, and electronic switching properties [17][18][19][20][21][22][23].The majority of the reactions between carbon disulfide and N-nucleophiles involve addition of carbon disulfide to N-H bonds. The products of these reactions, dithiocarbamate salts, reacts with epoxides [24, 25], 2-chloro-1,3-dicarbonyl compounds [26], chloroacetic acid [27], diethyl 2-chloromalonate [28], ethyl bromopyruvate [29], α-haloketones [30], 3,4-dihydro-2H-pyran [31], electrondeficient alkenes [32], β-nitrostyrene derivatives [33], dibenzoylacetylene [34], quinones [35], and itaconic anhydride [36] that can be transformed into dithiocarbamate derivatives.

To the best of our knowledge, there has not been any report on the reaction between carbon disulfide and amines in the presence of arylidenemalononitriles.

…”
mentioning
confidence: 99%
“…explored as new materials because of their superconducting, optical, and electronic switching properties [17][18][19][20][21][22][23].…”
mentioning
confidence: 99%